2009
DOI: 10.1111/j.1365-2141.2008.07513.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of adults with ALL

Abstract: SummaryThe cure rate of acute lymphoblastic leukaemia (ALL) in adults remains unsatisfactory. The remarkable progress in childhood ALL has not been replicated in adult ALL and approximately two thirds of patients younger than 60 years, and more than 90% of those over 60 years, are expected to succumb to their disease. Over 80% of adults can achieve a complete remission; however, the majority of such patients relapse. Nevertheless, significant developments have occurred over the past decade. Prognostic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 96 publications
(115 reference statements)
0
28
0
Order By: Relevance
“…3 The negative impact of age ⩾ 60 years was also reported in patients with Non-Hodgkin-lymphoma, ALL and Hodgkin lymphoma. [4][5][6][7] Among the reasons for the inferior survival in elderly patients are increased chemotherapy-related toxicities and adverse disease biology. 8 The introduction of reduced intensity conditioning (RIC) regimens in allogeneic HCT allows the use of this treatment even in older, comorbid or heavily pretreated patients and therefore enables a curative therapeutic option in patients who are not the candidates for HCT using a myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…3 The negative impact of age ⩾ 60 years was also reported in patients with Non-Hodgkin-lymphoma, ALL and Hodgkin lymphoma. [4][5][6][7] Among the reasons for the inferior survival in elderly patients are increased chemotherapy-related toxicities and adverse disease biology. 8 The introduction of reduced intensity conditioning (RIC) regimens in allogeneic HCT allows the use of this treatment even in older, comorbid or heavily pretreated patients and therefore enables a curative therapeutic option in patients who are not the candidates for HCT using a myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…In adult ALL, the overall complete remission (CR) rate of 85% to 90% is very high 3,[5][6][7] and confirms the efficacy of induction regimens with relatively low toxicity, which allow a very high percentage of patients to receive postremission therapy. Therefore, the problem with this disease is relapsing from remission, despite the fact that, as in pediatric ALL, the treatment is initially very intensive throughout induction and consolidation, and the maintenance treatment typically goes on for an additional 2 years or more.…”
mentioning
confidence: 95%
“…Rowe reported that long-term survival after intensive chemotherapy in patients over 60 was B10%. 7 This was Abbreviation: DFS, disease-free survival; EFS, event-free survival; OS, overall survival; SCT, stem cell transplantation. a Mentioned here are patients who received the therapy according to protocol, that is, within predefined time frames; many patients got the treatment with delay (see also 'off therapy due to delay' and 'of whom definitively' in the next row); all together, 20 patients received allogeneic SCT (allo-SCT) and 21 received maintenance therapy.…”
mentioning
confidence: 99%